An Open‐Source Laboratory Manual for Introductory, Undergraduate Soil Science Courses. Issue 1 (23rd August 2017) - Moorberg, Colby J.; Crouse, David A.
Abstract : Core Ideas: The Soils Laboratory Manual is a blueprint for open‐source laboratory resources. The Soils Laboratory Manual saves students a combined $12, 410 per semester. Open lab manuals should be optimized for laptop screens and printed copies. Instructors can develop course‐specific resources using this open‐source lab manual. High textbook cost is a major obstacle to affordable higher education. Open textbooks present one solution, but open laboratory manuals must be developed for lab‐based courses to successfully reduce overall textbook costs. Here, we present the Soils Laboratory Manual, an open‐source lab manual for undergraduate, introductory soil science courses. The manual facilitates the ability for instructors to develop their own editions of the manual customized for their specific course, teaching style, students, or even local soils. The manual was implemented in AGRON 305, an introductory soil science course at Kansas State University. During the fall 2016 and spring 2017 semesters, 213 AGRON 305 students responded to a survey that included questions regarding textbook costs, open textbooks, textbook format, and the Soils Laboratory Manual . Of students surveyed, 62% had forgone purchasing required textbooks due to cost, demonstrating a clear need for textbook alternatives. Overall, the Soils Laboratory Manual was well received. Based on student preferences, lab manual formatting should be optimized for printed copies, or for PDFs viewed using laptops. Adoption of the Soils Laboratory Manual saves AGRON 305 students a cumulative $12, 410 per semester. Similar savings are expected as new editions are developed for other soils courses across the United States and abroad. The Soils Laboratory Manual serves as a model for developing open‐source resources for natural science courses.